Reduction of internal carotid artery intima-media thickness in patients with moderate-to-severe obstructive sleep apnea syndrome after nasal surgery and uvulopalatopharyngoplasty. (3rd May 2016) - Peng, Yikun; Zhang, Liangchun; Hu, Defeng; Dai, Yubing; Wang, Shuhui; Liao, Hongyong; Xiong, Yan
Abstract: Conclusion Multi-level surgeries for the nasal cavity and palate can reduce the severity of obstructive sleep apnea with major narrowing above the retropalatal airway and reduce the carotid intima-media thickness, which can provide cardiovascular benefits to patients.Objective To evaluate the outcomes of moderate-to-severe obstructive sleep apnea syndrome by surgeries and the change of internal carotid artery intima-media thickness after surgeries.Subjects and methods Sixty-four patients with obstructive sleep apnea, narrowing at the nasal cavity, and retropalatal airways were enrolled in this study. Fifty-two patients underwent nasal surgery and modified uvulopalatopharyngoplasty. Twelve patients who refused surgeries and continuous positive airway pressure treatment received only conservative treatment. All patients were evaluated within 1 month before and 6 months after treatment using polysomnography, upper airway endoscopy, and B mode ultrasound.Results The success rate was 61.5% (32/52 patients) in the surgery group. There were significant differences between the surgery group and non-surgery group 6 months after treatment in the apnea hypopnea index, minimum and mean oxygen saturation, blood pressure, triglyceride, total cholesterol, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and internal Carotid intima-media thickness. The changes in the oxygen saturation and the apnea hypopnea index showed significant correlations with the changes in the intima-media thickness.